Effect of office technology on employees' health at Petronas Fertilizer (Kedah) Sdn. Bhd. (non-production) / Jawariah Abdul Rani, Mashitoh Yakob and Siti Norain Md Rodzi - Abdul Rani, Jawariah; Yakob, Mashitoh; Md Rodzi, Siti Norain (2009)
The researchers examined the effects of using office technology such as computer, telephone, printer, photocopier, scanner and fax machine on the employees' health at Petronas Fertilizer (Kedah) Sdn. Bhd. that focus on non-production employees. Nowadays, all offices throughout the world use technology in its work in order to make it easier and faster. But, many employees do not realize that some of the equipment can affect their health. The effects of using computer include the illness to the employees and the risks to their health. In this research the researchers provided the preventions and the solution to the problem. The employees' awareness on the effects from using the equipment is very low. They do not realize that their healths will suffer if they take for granted about the radiation from the equipment that they used. The data were obtained from questionnaires which consist of convenience sampling. The questionnaires were distributed to the non production employees who worked with office technology equipments in the company. The researchers found that most of the employees contributed to the experience in any pain such as numbness, or tingle in their wrist, hand or finger, headache, neck and back injuries or arm injuries because of computer uses. But, the researchers also found that the majority of the employees who work using the office equipment such as computer in the long period of time did not have a problem with their vision. This is because they practise a healthy and safety steps during working with the equipments such as using a screen filter for their computer, use ergonomic chairs or desk and choose the best size and weight of their laptop.